What Determines HIV Prevention Costs at Scale? Evidence from the Avahan Programme in India - Lépine, Aurélia (Health Econ, 2016)
Expanding essential health services through non‐government organisations (NGOs) is a central strategy for achieving universal health coverage in many low‐income and middle‐income countries. Human immunodeficiency virus (HIV) prevention services for key populations are commonly delivered through NGOs and have been demonstrated to be cost‐effective and of substantial global public health importance. However, funding for HIV prevention remains scarce, and there are growing calls internationally to improve the efficiency of HIV prevention programmes as a key strategy to reach global HIV targets. To date, there is limited evidence on the determinants of costs of HIV prevention delivered through NGOs; and thus, policymakers have little guidance in how best to design programmes that are both effective and efficient. We collected economic costs from the Indian Avahan initiative, the largest HIV prevention project conducted globally, during the first 4 years of its implementation. We use a fixed‐effect panel estimator and a random‐intercept model to investigate the determinants of average cost. We find that programme design choices such as NGO scale, the extent of community involvement, the way in which support is offered to NGOs and how clinical services are organised substantially impact average cost in a grant‐based payment setting. © 2016 The Authors. Health Economics published by John Wiley & Sons Ltd.